KEPEMIMPINAN PEMBELAJARAN KEPALA SEKOLAH DALAM IMPLEMENTASI KURIKULUM 2013 - Iriyanti Iriyanti (UNIVERSITAS BENGKULU, 2015)
The objective of the research is to describe the implementation of instructional leadership on 2013 curriculum implementation by school principal. The research used qualitative method. The subject of the research is school principal, the vice principal, teachers, and some of the student. Data was collected by interview, observation, and documentation. The result showedthat: (1) the school principal guided the teacher on making lesson plan; (2) the school principal gives more focus on learning activity aspect; (3) the principal gives learning evaluation guidance by using learning observation technique in the class.; (4) the principal has not maximized on theguidance of learning evaluation and monitoring because of the limited time and knowledge.Keywords: leadership, school, principal, curricullum 2013, implementation